2018
DOI: 10.1101/449983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cyclin A – Myb-MuvB – Aurora B network regulates the choice between mitotic cycles and polyploid endoreplication cycles

Abstract: SummaryCells switch to polyploid endoreplication cycles during development, wound healing, and cancer. We used integrated approaches in Drosophila to determine how mitotic cycles are remodeled into endoreplication cycles, and how similar this remodeling is between developmental and induced endoreplicating cells (devECs and iECs). We found that while only devECs had a dampened E2F1 transcriptome, repression of a Cyclin A - Myb-MuvB - Aurora B mitotic network promoted endoreplication in both devECs and iECs. Cyc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 90 publications
(130 reference statements)
3
14
0
Order By: Relevance
“…Similar to what has previously been reported, we identified an enrichment of cell cycle genes directly regulated by Myb, with the majority being G2/M but also several S phase genes (consistent with studies on B-Myb, supporting its role in S phase; Lam et al, 1992;Werwein et al, 2012). Notably, a recent study reported that Cyclin A (the cyclin that regulates aspects of both S phase and G2/M) directly binds to Myb and is required for expression of many of its targets (Rotelli et al, 2019). Further supporting a role for Myb in transcriptional regulation, we find that Myb is required for optimal levels of H3K4 promoter methylation, with Myb playing a key role in RNA Pol II dynamics.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to what has previously been reported, we identified an enrichment of cell cycle genes directly regulated by Myb, with the majority being G2/M but also several S phase genes (consistent with studies on B-Myb, supporting its role in S phase; Lam et al, 1992;Werwein et al, 2012). Notably, a recent study reported that Cyclin A (the cyclin that regulates aspects of both S phase and G2/M) directly binds to Myb and is required for expression of many of its targets (Rotelli et al, 2019). Further supporting a role for Myb in transcriptional regulation, we find that Myb is required for optimal levels of H3K4 promoter methylation, with Myb playing a key role in RNA Pol II dynamics.…”
Section: Discussionsupporting
confidence: 88%
“…S1, O–Q ′). Given that CYCA knockdown can induce endo-reduplication ( Rotelli et al, 2019 ), we performed EdU staining on control and CYCA RNAi germaria. GSCs with a round spectrosome and decondensed DNA are EdU negative and can therefore be considered in G2/prophase ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Follicle cells undergo three endocycles, resulting in a ploidy of 16C. Previous work has shown that there are distinct changes in genome regulation during the endocycle, including a global decrease in transcription, decrease in E2F1 target gene expression, and acquisition of endocycle-specific ORC binding sites (Maqbool et al 2010; Sher et al 2012; Hua et al 2018; Rotelli et al 2019). Therefore, we hypothesized that follicle cell replication timing may be influenced by this developmentally regulated cell cycle transition.…”
Section: Resultsmentioning
confidence: 99%